Complex Magnetic Reversal Modes in Low-Symmetry Nanoparticles - Altbir-Drullinsky, D; Allende-Prieto, S; Escobar-Donoso, R; Vargas-Ayala, N; Castillo-Sepulveda, S (American Institute of Physics, 2014)
A detailed numerical analysis of the magnetization reversal processes in T-shaped nanoparticles has been carried out. Attention has been focused on the influence of the symmetry of the particle on the formation, propagation, and interaction of internal magnetic structures such as domain walls, vortices, and antivortices. Results show that the lower the degree of symmetry of the particle, the more complex the reversal process is. Thus, symmetry represents an additional ingredient to control the magnetic properties of ferromagnetic nanoparticles. © 2014 AIP Publishing LLC.